Analisis Peran SDM Yang Kompetitif Sebagai Penentu Keberhasilan Dan Pengembangan Usaha Dalam Koperasi Sumber Berkat Abadi Maumere - Maria Rasdiana Bure; Dwi Ainul Mardiah Rachman; Hildensia Dortiana Daba; Maria Imelda Ero Wuwur; Ita Sulfiana Sari; Nunsio Handrian Meylano (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
This study aims to analyze the role of competitive human resources (HR) as a determinant of business success and development at the Sumber Berkat Abadi Maumere Cooperative. The method used was descriptive qualitative through interviews, observations, and document review. The results indicate that the implementation of competitive HR is carried out through development, training, performance management, and vision-mission-based strategies. The main factors supporting competitiveness are competence, education, motivation, discipline, innovation, communication, work ethic, work environment, and leadership. Indicators of success are evident in the expansion of branches to several regions and high public trust. Obstacles identified include the lack of a written performance appraisal system and limited technology-based training. This study concludes that competitive HR is the key to the cooperative's progress.